Integrated Evaluation of Potential Trace Elements and Pollution Indices in Wadi El-Natrun Saline Lake, Egypt: A Multidimensional Approach to Aquatic Ecosystem Health - Ali, Mohamed H. H.; Abdelkarim, Mohamad S.; Salem, Salem G.; Al-Afify, Afify D. G. (Water, air, and soil pollution, 2025)
The accumulation of potential trace elements (PTEs) in water, sediment, and two fish species from El Bieda saline Lake, Wadi El-Natrun, Egypt was assessed to highlight the environmental status and health implications of these elements. Most PTE levels in lake water remained below the permissible limit, except for lead, selenium, and mercury which exceeded safety thresholds. Notably, sites B1 and B2 attained the highest PTEs concentrations in water and sediment, surpassing permissible limits for cadmium, mercury, and arsenic. The contamination factor (C f ) values for most PTEs were less than 1, indicating minimal pollution. The mean contamination degree (mCd) values varied from 0.5–0.70 suggested uncontaminated grade. The potential ecological risk index (PERI) values were less than 40, suggesting low potential ecological risk except for Hg. The flesh and liver of Oreochromis aurous and Tilapia zillii presented PTEs levels below permissible limits, except for lead, cadmium, arsenic, and chromium. O. aurous accumulated more PTEs than T. zillii . Despite the presence of PTEs, the estimated daily intake (EDI) and target hazard quotient (THQ) values remained below harmful thresholds, indicating no immediate health risks from fish consumption. These results underscore the need for ongoing management strategies and continuous monitoring to address the accumulation of hazardous trace elements in the ecosystem, thereby protecting environmental health and public safety.